Kebijakan Hukum Dalam Mengoptimalkan Pendapatan Asli Daerah di Kota Pekanbaru (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This scientific work assignment discusses legal policies in optimizing local original income in the city of Pekanbaru. This research aims to explore an in-depth understanding of the role of legal policy in increasing local revenue in the region. In this study, an analysis of the applicable rules and regulations and their impact on potential regional financial revenues was carried out. The research methodology used includes document analysis, interviews, and comparative studies with similar cities. The results of this research can provide a clearer view of the importance of legal policy in supporting regional economic growth and provide recommendations for further improvement. It is hoped that this research will be an important contribution to the practical and academic understanding of this issue in the Pekanbaru city.